Utilization of Wild Plants As Alternative Food and Medicine For The Dayak Kendawangan Siakaran, Randai Village - Deani Rizqy Shafhira Putri; Dede Mulyanto; Budiawati Supangkat (Endogami: Jurnal Ilmiah Kajian Antropologi, 2026)
This ethnobotanical study aims to document the local knowledge of the Dayak Kendawangan Siakaran community in Randai Village, Ketapang Regency, West Kalimantan, regarding the use of wild plants as alternative sources of food and medicine. This qualitative research used participant observation, semi-structured interviews, and questionnaires free listing against 23 informants. This study recorded 110 wild plant species from 44 families that are used as alternative food and medicine. The most widely used plant part is the fruit (46%). Most wild plants originate from native geographic states (native) Borneo (51%), followed by introductions (exotic) (45%), and endemic (4%). The primary habitat of these plants is predominantly forests and the surrounding village areas (fields, swamps, riverbanks), indicating intensive community interaction with the surrounding ecosystem. However, today the local biodiversity and culture of the community face serious threats from deforestation and land conversion. In response, the community carries out conservation practices based on local wisdom, such as transplanting wild plants in the yard.